ON CHARACTERISTIC FUNCTIONS OF CHECKING TESTS OF BINARY TABLES - Yeghiazaryan, Ed.V. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2015)
In the paper correspondence between the monotonic functions and the set of irredundant checking tests of binary tables is formed. The maximum number of irredundant checking tests of binary table is determined.
Keywords: test, checking test, irredundant test, monotone function